The Influence of PHBS Education in Preventing Infectious Diseases: Tuberculosis - Helmi Juwita; Nurwahita; Eva Yuliani; Muhammad Qasim (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Backround: Tuberculosis is a leading cause of death from infectious diseases. Clean and healthy living behavior or PHBS plays a crucial role in preventing infectious diseases, including tuberculosis is an infectious disease that remains a global health problem. This study aims to determine the effect of PHBS education on preventing infectious diseases: tuberculosis. Mhetod: This research was conducted in Konja Selatan Hamlet, Pamboborang, Majene Regency, West Sulawesi, in May 2025. Twenty-one respondents were recruited. The research instrument used a pre- and post-test knowledge questionnaire to measure respondents' knowledge before and after receiving PHBS education. Data were analyzed using frequency analysis of knowledge before and after receiving PHBS education. Results: prior to receiving PHBS education regarding the prevention of infectious diseases tuberculosis, the majority 71.4% had sufficient knowledge. Furthermore, 23.8% had good knowledge, while 4.8% had poor knowledge. Following the education, post-test results showed that the majority of the community's knowledge was good 62% and 38% had sufficient knowledge. Conclusions: PHBS education has an impact on preventing the infectious disease tuberculosis. The knowledge of the people of South Konja Hamlet increased after conducting outreach on preventing the spread of infectious diseases tuberculosis.